Research on the Bioactivity of Plant Essential Oils on Armyworm [Mythimna separata (Walker)] Larvae - Wang, Tao; Ren, Yanling; Zhao, Jinyu; Liu, Yao; Xu, Bin; Yang, Maofa; Zhao, Wanling; Zheng, Xinian; Wang, Juan; Deng, Liuqiong (Frontiers in Chemistry, 2022)
In order to find out the biological activity of plant essential oils on armyworm (Mythimna separata (Walker, 1865)) larvae and provide a theoretical basis for the biological control on armyworms, in this study, the antifeedant activity, repellent activity, fumigation activity, contact activity, and synergistic effect on indoxacarb of 9 kinds of plant essential oils on armyworm larvae were determined. The results showed that lavender and citronella essential oils had the greatest impact on the antifeedant activity on armyworm larvae, and the antifeedant rate reached 100.00%. Meanwhile, rosemary essential oil revealed the best repellent activity on armyworm larvae with an average dwell time of 0 s at the content of 0.2%. Moreover, tea tree essential oil and lemon essential oil at the content of 2.0% had the best fumigation and contact activity against armyworm larvae, the corrected mortality rates at 120 h were 86.67% and 66.67%, respectively. In addition, the combination of citronella essential oil and indoxacarb with the ratio of 5:1 had the best synergistic effect on armyworm larvae at 96 h, and the synergistic ratio was reached 100.00%. These findings will guide the development of new insecticides for controlling armyworm larvae.